Central Heating Control Charts for the Economic Use of Energy in Residential Buildings - Bargłowski, Leszek; Adamski, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Methods and types (qualitative, quantitative or mixed) of control of central heating installations in residential buildings are presented. Measurements were made for a radiator in a central heating system that was powered by a heating node substation. The output temperature of the heat node supplying the residential building, in which the test stand was located, was compared with the measured supply and return temperature. Indoor room temperature, outdoor air temperature, inflow and outflow temperature on the vertical supplying the heater were also recorded and analysed.
Keywords: heater; thermal power; heating system; supply temperature; control diagrams